Frequency of Intestinal Tuberculosis in Patients with Acute Abdomen - Muhammad, Faqir; Haque, Anwar Ul (Biological and Clinical Sciences Research Journal, 2025)
Intestinal tuberculosis remains an important but often underrecognized cause of acute abdomen in tuberculosis-endemic regions, leading to diagnostic delay and increased morbidity. Objective: To assess the frequency of intestinal tuberculosis among patients presenting with an acute abdomen. Methodology: This study was conducted on 92 patients aged 18 to 65 years who presented with an acute abdomen. These patients were assessed for intestinal TB. Intestinal TB was confirmed through clinical examination, along with a CT scan showing terminal ileum asymmetric wall thickening, cecum, and ileocecal valves associated with necrotic lymph nodes. SPSS 25 was used for data analysis. Results: The mean age of the patients in the present study was 38.86 + 13.66 years. Fifty-three were (57.6%) male, and 39 (42.4%) were female. The frequency of intestinal tuberculosis was 12 (13.0%). Intestinal TB was notably associated with age > 50 years, malnutrition, low economic background, and pulmonary TB. Conclusion: Intestinal tuberculosis was identified in 13.0% patients presenting with acute abdomen. Intestinal TB showed a significant association with malnutrition, low economic background, and pulmonary TB.